Intermediate water ventilation in the Nordic seas during MIS 2. Issue 9 (12th May 2013) - Rørvik, Kari‐Lise; Rasmussen, Tine L.; Hald, Morten; Husum, Katrine
<x xml:space="preserve">Abstract</x> [1] A high‐resolution marine record from the northern Norwegian continental margin off Lofoten is used to reconstruct changes in the oceanography of the Nordic seas during marine isotope stage (MIS) 2 including the Last Glacial Maximum and early deglaciation circa 25 to 16 ka. The period was characterized by generally warm subsurface water temperatures >2°C and inflow of Atlantic surface water. Several events were characterized by decrease in ventilation of the intermediate water and low subsurface temperature and salinity. They correlate with colder atmospheric temperatures as seen in ice cores. The events terminated with gradual strengthening of the intermediate water ventilation and increase in subsurface temperature. The generation of intermediate water was unstable and experienced climate and ventilation changes on millennial and centennial timescales. The changes appear consistent with modeling experiments that predict short‐lasting circulation stops during MIS 2 due to release of meltwater in the Nordic seas.